Justice and security in the united nations: between politics and international law - Horna Chicchón, Angel Valjean (2024)
The article presents some interactions between politics and international law, based on a perspective of international law as a decision-making process in appropriate fora (New Haven School), in particular the UN and its main organs (the General Assembly and the Security Council). After outlining the relationship between international law and politics in the context of the progressive development of international law and its codification, the article elaborates some ideas through two main parts: international criminal justice and collective security. Regarding international criminal justice, while mechanisms exist to guarantee and reinforce it as a response to the abusive exercise of power and force, political issues inevitably affect the efforts of the international community. Regarding the collective security system, the author highlights the crisis it is going through due to geopolitical divisions and mistrust among some of the permanent members of the Security Council. The author concludes that without prejudice to the threats to multilateralism and despite the instrumentalization of international law, its defense and validity are critical to achieve the necessary balances in the current scenario of fragmentation and possible transition to a new world order, based on a more inclusive, equitable and representative system.